Social determinants of health - Marmot, M. G.; Wilkinson, Richard G. (Oxford : Oxford University Press, 2006)
This text gives an authoritative overview of the social and economic factors which are known to be the most powerful determinants of population health in modern societies.
Prevous ed.: Copenhagen: World Health Organization, 1998.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health -- Social aspects; Social medicine; Medical policy; Health status indicators